Erythropodium caribaeorum (Duchassaing and Michelotti, 1860) (Cnidaria: Alcyonacea), an additional alien coral in the Southwestern Atlantic - Carpinelli, Ágatha Nascimento; Cordeiro, Ralf Tarciso Silva; Neves, Leonardo Mitrano; de Moura, Rodrigo Leão; Kitahara, Marcelo Visentini (Zootaxa, 2020)
Invasive species may compromise biodiversity and ecosystem services, and represent a steadily growing concern for coastal marine ecosystems. The marine aquarium trade (MAT) is the source of some of the world’s worst aquatic invasions, inflicting multimillion-dollar losses in infected regions. In the Southwestern Atlantic (SWA), two Indo-Pacific coral species were recently introduced as a result of the MAT and already dominate the substrate at the introduction site in Southeastern Brazil (Praia Vermelha, Angra dos Reis, Rio de Janeiro State). Herein, based on morphological and molecular evidence, we report a Caribbean native coral species likely introduced by the MAT in Praia Vermelha, Erythropodium caribaeorum (Duchassaing & Michelotti 1860). While the eradication of coral species that already have a pest status in the SWA is unlikely, we propose that the eradication of the three species still contained to their introduction sites, including E. caribaeorum, is still feasible and depends on a rapid and integrated embracement of the task by core stakeholders. Priority actions for the regulation of MAT and hobbyism in Brazil are proposed.